Progresso espaço-temporal da mancha aureolada em mudas de cafeeiro no viveiro - Oliveira, Júlia Marques (2017)
Bacterial blight in coffee (Pseudomonas syringae pv. garcae) has frequently occurred in nurseries and crops, causing producers and technicians to worry about considerable losses and being difficult to control. In order to better understand the progress of epidemics, the origin and quantity of the initial inoculum, the forms of pathogen dissemination, the influence of climatic, and environmental factors on the infection as well as on the spread of pathogens, it is necessary to know the spatial distribution of diseased plants. Besides, it will help to understand and to propose new disease management practices. Considering this, the objective of this project is to evaluate the temporal space progress of the bacterial b light in coffee tree seedlings. The experiment was carried out in a nursery in Lavras-MG, where three beds were delimited (1.05 m wide and 2 m long), containing 496 seedlings each, arranged in rows (16) and columns (31). Coffee plantlets of Catuaí Vermelho cultivar IAC 99 were grown in polyethylene bags (0.065 m in diameter by 0.20 m in height) filled with substrate. When the seedlings reached the first pair of leaves, four seedlings inoculated with the P. syringae pv. garcae with symptoms of the bacterial blight were introduced in the bed center. There were epidemics in the beds 15 days after the introduction of the initial inoculum with duration of six weeks, and maximum value of 6% of incidence. There was spatial dependence, and the disease reached up to 55.18 cm away. The higher the number of hours with leaf wetting during four consecutive days, together with lower values of wind speed for more than eight days, the greater the incidence of the bacterial blight in coffee seedlings in the nursery.